Clinical efficacy of bronchoalveolar lavage in the treatment of small airway diseases in children - Zhou, Lili; Peng, Xuyun; Cao, Liqin; Zhang, Lin; Xiang, Huazheng (Frontiers in Pediatrics, 2024)
Objective To evaluate the efficacy of bronchoalveolar lavage (BAL) in the treatment of children with small airway diseases. Methods Children (n=112; male:76, female:36 [ratio 2.1:1]; age range: 1 month-10 years; median age:12 months) with small airway diseases diagnosed by high-resolution computed tomography (HRCT) were enrolled in this study. The patients were assigned to either the BAL group (BAL and conventional therapy) or the control group (conventional therapy only). The duration of cough, fever, wheezing, hospitalization duration, disease course before admission, treatment cost, HRCT recovery time, and re-hospitalization rate were compared between the two groups.The median disease course before admission of the BAL group patients was longer than that of the controls (p=0.006). The duration of cough and wheezing in the BAL group was significantly longer than those in the control group (p=0.012 and p=0.001, respectively). The recovery time of cough, the re-hospitalization rate, and the total expenditure incurred on the BAL group were lower than those for the control group (p=0.027, p=0.026, and p=0.000, respectively).At 2 months after discharge, the small airway lesions were found to be absorbed in 86.2% of BAL group patients versus 64.1% of control group patients. At 6 months after discharge, the lesions were not fully absorbed in 3.4% of the BAL group patients when compared with 20.5% in the control group patients.Conclusion BAL is suitable for patients with a long disease course before admission, long duration of coughing, and recurrent wheezing. BAL treatment of small airway diseases in children can promote the disappearance of clinical symptoms, accelerate the improvement of imaging, reduce the rate of re-hospitalization, and reduce the cost of treatment.